2019
DOI: 10.1111/1751-7915.13505
|View full text |Cite
|
Sign up to set email alerts
|

Control of solvent production by sigma‐54 factor and the transcriptional activator AdhR in Clostridium beijerinckii

Abstract: Summary Clostridia are obligate anaerobic bacteria that can produce solvents such as acetone, butanol and ethanol. Alcohol dehydrogenases (ADHs) play a key role in solvent production; however, their regulatory mechanisms remain largely unknown. In this study, we characterized the regulatory mechanisms of two ADH‐encoding genes in C. beijerinckii. SigL (sigma factor σ54) was found to be required for transcription of adhA1 and adhA2 genes. Moreover, a novel transcriptional activator AdhR was identified, which bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…The strains expressing AdhRΔGAF and AdhRΔGAFΔPAS also exhibited enhanced acetone synthesis, which may be due to indirect regulation of the genes involved in acetone synthesis (36). Combination of AdhR truncation and SigL overexpression could lead to a further increase in solvent production by C. beijerinckii (13).…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations
“…The strains expressing AdhRΔGAF and AdhRΔGAFΔPAS also exhibited enhanced acetone synthesis, which may be due to indirect regulation of the genes involved in acetone synthesis (36). Combination of AdhR truncation and SigL overexpression could lead to a further increase in solvent production by C. beijerinckii (13).…”
Section: Figmentioning
confidence: 99%
“…However, little is known about the regulatory mechanisms that maintain redox balance in other clostridia, such as C. beijerinckii. In our previous study, the sigma factor 54 (SigL) and the transcriptional activator AdhR were found to control alcohol synthesis in C. beijerinckii (13). 54 is required for transcription of adhA1 and adhA2 genes, encoding alcohol dehydrogenases (ADHs).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Creating mutants that are resistant to adverse environments Engineering TF is a way to create strains capable of producing organic solvents that are generally toxic to microbes. 65 Regulating the transcription step by manipulating TF is also a feasible method to confer microbes more resistant to adverse situations. 34 Although TF primarily functions in transcription, its influence can be associated with diverse cellular processes via proteins or noncoding RNAs.…”
Section: Application Of Engineered Tfs Constructing Inducible Expressmentioning
confidence: 99%